LKAB’s Straight Grate Process - Examining new Process Concepts - Nilsson, Johan (Chalmers tekniska högskola / Institutionen för rymd-, geo- och miljövetenskap, 2018)
LKAB is one of Sweden’s larger industrial companies and is, on the seaborne import market, the second largest supplier of iron ore pellets in the world. Mining and processing iron ore are energy intensive processes with considerable energy related emissions. The final heat treatment of the iron ore pellets, done in a straight-grate or grate-kiln furnace, is the most energy intensive part of the process. A collaboration between LKAB and the Division of Energy Technology at Chalmers aims to improve the energy efficiency of the heat treatment in the pelletizing plants. This thesis, as a part of that initiative, investigates the possibility to improve the energy efficiency of the straight-grate process. By modifications to a previously developed model for simulating the heat treatment in the straight-grate process, several design concepts are investigated in this work. The evaluation is based on performance indicators and process constraints with input data from the MK3 unit in Malmberget. The most interesting concepts identified are optimized towards either production rate or fuel consumption, with a sustained product quality. The results indicates that a prolonged drying section is the most promising concept. An increase in production rate of 6 % is achieved with a reduced fuel consumption by 32 %. If the process is optimized solely for fuel economy a reduction of 50 % may be achieved. Furthermore, this work shows that development of the simulation model is required to properly be able to simulate the straight-grate process, where implementation of leakage flows between process zones and a wider range of quality parameters are the most important areas.